Developing a hierarchical model to enhance business excellence in hotel industry of Bangladesh - Rahman, Mahbubar; Islam, Rafikul; Wan Husain, Wan Rohaida; Ahmad, Khaliq (Emerald, 2019)
Purpose –This study develops a hierarchical model based on Malcolm Baldrige National Quality Award (MBNQA) that enables ranking of a number of quality dimensions for achieving business excellence in the hotel industry of Bangladesh. Design/methodology/approach – The study adopted a sequential mix method approach wherein semi-structured interviews with 24 participants were initially conducted in the qualitative stage to identify the quality dimensions. Subsequently, a questionnaire survey was carried out on 40 industry experts to prioritise the identified elements using the relative measurement of the Analytic Hierarchy Process (AHP), and 32 respondents were further surveyed to evaluate a selected number of hotels in Bangladesh applying the absolute measurement of AHP. Findings – The study uncovered 8 criteria during the qualitative stage together with 23 of their corresponding sub-criteria. Quality management emerged as the most crucial criterion, and a health and safety-security measure was the most important sub-criterion in addressing this criterion. It was also found that five-star hotels are performing well in Bangladesh compared to three-star and four-star hotels. Originality/value – The developed model is the unique one which can be used by Bangladeshi practitioners to measure performance of hotels. Moreover, it can be applied to measure performance of hotels in other countries as well with minor modification in the model framework.